MOTIVASI INVESTASI, FINANCIAL LITERACY, DAN PERSEPSI RESIKO PENGARUHNYA TERHADAP MINAT BERINVESTASI DI PASAR MODAL - Hikmah Hikmah (Universitas Bina Bangsa, 2021)
Indonesia is one of the countries where financially most of the population continues to make short-term investments or save. If you look at the difference with some very developed countries, the investment is in the long term or investment. The existence of public understanding of financial management so that people are able to set aside a portion of the income earned in conducting investment activities. At present, there are many financial effects that exist both in the money market and in the capital market, for example in the money market such as savings and time deposits, while in the capital market there are securities such as bonds and shares from various companies or government owned. This study aims to determine investment motivation, financial literacy and risk perception of its influence on public investment interest in the capital market in Batam City. The population in this study is the sub-district of Sagulung, with 204 respondents as the sample in this study. The respondents in this study are people who are interested in investing in the capital market. The sampling technique used is purposive sampling. The analysis method used is SEM with the SmartPLS application. The results show that investment motivation has a positive and significant effect on investment interest, financial literacy has a positive and significant effect on investment interest, risk perception has a positive and significant effect on investment interest in Batam city